Housusukissa haudatut – Rengassolkia Koroisten kirkkomaasta - Harjula, Janne (Suomen Keskiajan Arkeologian Seura, 2025)
The paper discusses the circular buckles found in pairs from some burials excavated in Koroinen, a 13th–14th century episcopal see site in Turku, SW Finland. Based on the comparative archaeological material from Britain and elsewhere in Europe, the buckles most probably represent hose buckles i.e., they attached the hose to the undergarment of the male dress using buckles and straps. The finds seem to represent dress accessories of men with a high ecclesiastical status, and who were buried fully clothed, unlike common people who usually got a modest, shrouded burial. Furthermore, the circular buckles found in Koroinen seem to be the first archaeological indication of the use of hose as part of the men’s clothing in medieval Finland.
Shattered and Scattered Pasts: Festschrift for Professor Georg Haggrén